Elaboración de modelo de Gestión de mantenimiento para los equipos y edificios del Villas Sol Hotel & Villas Beach Resort - Durán-Gutiérrez, Marcos Aurelio (Instituto Tecnológico de Costa Rica, 2017)
The competitiveness in the hotel sector of the province of Guanacaste, makes that the companies focus on the implementation of improvements, with the purpose to encompass more market, in such a way that improves the productivity of these organizations. In order to present improvements in production, it is necessary that all departments commit to continuous improvement, so that each of them, however small, will provide a considerable contribution to the organization. This is one of the main motivations for the maintenance department of the Villas Sol Hotel & Villas Beach Resort has decided to implement a high level engineering project, with which considerable improvements can be presented and add value to the company. This project proposes the elaboration of a Maintenance Management Model, with which it is possible to supply the maintenance needs of the equipment and buildings. It is intended to propose other improvements, with which it is possible to give a contribution beyond the objectives of the project, in a way that generates value for the organization with these extra contributions. This project starts with an analysis of the maintenance management of the maintenance department, identifying deficiencies in infrastructure, personnel, and administrative maintenance processes. Initially, the mission and vision of the department are planned, as well as a restoration of the necessary personnel to fill the working days, which is a vital point for the Project. Applying the regulations COVENIN 2500-93, it was possible to identify the strengths and the decreases in the different areas of study of the norm and thus to determine the solutions for the problems identified. 4 The next part of the maintenance management model defines the components of the model and their relationship, so that management is appropriate to the production process. After this, the administrative processes of maintenance were designed, including a system of work orders, flow charts, inventory control of materials, equipment and documentation of failures. A preventive maintenance plan was created for the equipment in which it was feasible to apply this technique, by identifying the maintenance needs of equipment and buildings, also defining the different inspection routines, the frequency of assignment and the programming through an annual Gantt. Subsequently, the technical and financial indicators were defined by Balanced Scorecard, the acceptance ranges, calculation formulas and each of the fields necessary for the correct application of the BSC were defined in its four perspectives (financial, internal processes, client And learning and growth). As a final part of the project, see a preliminary sketch of the distribution of the buildings according to the needs that were detected during the practice, a program was proposed 5 S for the maintenance manager's office and that in the future it Throughout the department and throughout the company.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2017.
Keywords: Hotel; Mejora continua; Mantenimiento; Balanced Scorecard; 5 S